THE EFFECT OF 'SADARI' HEALTH EDUCATION ON EARLY BREAST CANCER DETECTION KNOWLEDGE AMONG FEMALE TEENAGERS AT SMAN 1 GIRI TARUNA BANGSA BANYUWANGI - Nur Hidayatin; Ukhtul Izza; Diana Kusumawati; Rani Diana Balqis; Indah Christiana; Ferlina Vidiastuti (JOURNAL EDUCATIONAL OF NURSING(JEN), 2026)
Breast cancer represents a prevalent malignancy characterized by the growth of cancerous tumors within the mammary tissue. Annually, new diagnoses exceed 185,000 cases among women, with a rising incidence trend observed in developed nations. Accounting for approximately 43,500 annual fatalities, it ranks as the second most frequent cause of cancer-related mortality in women, following lung cancer. Consequently, the role of Breast Self-Examination (BSE) is acknowledged as a vital factor in enhancing students' knowledge for the early detection of the disease. This study employed a quantitative approach utilizing a pre-experimental research design. Data collection was facilitated through a questionnaire to evaluate knowledge levels and an observation checklist to assess practical skills. Using a simple random sampling technique, a total of 68 participants were recruited. Following data processing via the Wilcoxon signed-rank test, the findings demonstrated that a vast majority of respondents specifically 62 individuals (91.2%), attained a high level of knowledge regarding SADARI after the intervention. Meanwhile, 6 individuals (8.8%) had an adequate level of knowledge about SADARI. From the statistical test of knowledge and ability before and after health education, a p-value of 0.000 (p <0.05) was obtained. This confirms that health education significantly influences the knowledge of students at SMAN 1 Giri Taruna Bangsa regarding SADARI. Such findings highlight the efficacy of school-based education in promoting early breast cancer screening. It is expected that the school will always conduct health awareness programs for women and collaborate with health workers, especially regarding SADARI examinations.